Social dialectisms: history and theory of working out (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article is examined the phenomenon of social dialects in a historical aspect. An attempt was made to systematize theoretical material of world and native social linguistics.
Keywords: social dialect (sociolect); social dialectizm (sociolectizm); argo; jargon; slang